(untitled) (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To compare the radiological and functional outcome of stable intertrochanteric femur fractures treated with Dynamic Hip Screw(DHS) and Proximal Femoral Nail(PFN). Methods: This randomized controlled trial was conducted in Department of Orthopaedics Pakistan Railway General Hospital Rawalpindi from 20th March 2018 and 19th March 2020. All patients with stable intertrochanteric fractures fulfilling the inclusion criteria were randomly allocated to group A(DHS) and B(PFN). Patients were reviewed radiologically for healing and functional assessment was done with Harris Hip Score(HHS) and graded as poor(score <70),fair( 70 to 80),good( 80 to 90) and excellent(90 to 100). Comparison of outcomes in both groups were done at 3rd,6th and 12th month and P value was calculated with independent sample t test and Chi-square test. P<0.05 was considered significant. Results: The total number of patients were 60.They were equally and randomly divided into group A and B with 30 patients in each. The mean age of group A was 59.20±5.94 years and group B was 58.80±6.67 years. Male patients were 19( 63.33% ) in group A and 17( 56.66%) in group B. Female patients were 11(36.66%) in group A and 13(43.33% ) in group B. The mean radiological union time in group A was 13.4±3 weeks while in group B 13.5±5 weeks(P>0.05). The Harris Hip Score(HHS) at 3 months follow up was 53.50±3.91(poor) and 34.93±3.98(poor) in group A and B respectively.(P< 0.05) At 6 months group A had HHS 89.37±4.03(good) and B 81.87±4.10.( P< 0.05)At one year HHS was 93.73±1.99(excellent) and 92.57±2.30(excellent) in group A and B.( P>0.05). Conclusion: For stable intertrochanteric fractures both DHS and PFN yielded similar outcome in terms of radiological union. The short term functional outcome of both DHS and PFN at 3rd and 6th was poor and good but DHS had statistically better score than PFN.At one year follow up both DHS and PFN had similar excellent functional outcome but without any statistically significant difference in the score.